Chains of securitization - Marieke de Goede (Finance and Society, 2017)
Securitization has a dual rationality that twins a financial sense to one of modern statecraft and national security. This forum contribution advocates a focus on material practices as a means of further exploring the entanglement of finance and security. In particular, it advances a notion of "chains of securitization", arguing that such a concept provides researchers with a concrete way to analyze how "financial" objects, such as derivatives, are assembled to generate (in)securities, as well as how 'security' objects, such as suspicious transactions, are assembled across public/private domains.
Keywords: 300